Identificación de sustratos proteicos en celulas humanas para proteínas ROP cinasas de Toxoplasma gondii (2017)
Summary Background: Toxoplasma secretes proteins known as ROP kinases; (ROPs) which are important for establishing the survival and growth of the parasite within the host cell. It has been shown that the Toxoplasma ROP5/ROP18 complex is the major effector related to virulence in mice. This complex specifically phosphorylates interferon-induced GTPases (IRGs). There is no evidence whether this complex or other ROP kinases are involved in the development of human toxoplasmosis. Aim: To search human substrates for Toxoplasma gondii ROP11, ROP39 ROP5 and ROP18 in a human cell line. Methodology 1a: We designed an algorithm called MSCA (Multiple Spectral Comparison Alignment) for the search of interactions between proteins (Toxoplasma and Human). 2a: recombinant proteins ROP11, ROP39, and GBP5 were cloned into pGEX4T1 and expressed in E. coli ROSSETTA DE3; with these proteins we performed Pull-down assays either with mass spectrometry (MS) or Western blot (WB). 2b: yeast 2 hybrids (Y2H) protein-protein interaction screening was performed between some ROPs and human GBPs 1-5. 2c: pro-IL1β levels were compared in human PBMCs infected ex-vivo with Toxoplasmas RH or RHΔROP18. Results 1a: MSCA proposed the interactions ROP11-SLC3A2, ROP11-ANXA6, ROP39-SHMT2, ROP39-ROP5, hGBP5-ROP5, and hGBP5-ROP18. 2a the interactions ROP11-SLC3A2, ROP11-ANXA6, ROP39-SHMT2, and ROP39-ROP5 were confirmed by Pull-down MS. 2b: the interactions hGBP5-ROP18 and hGBP5-ROP5 were observed in the yeast 2 hibrid (Y2H) screening interaction. The interactions ROP39-ROP5 and hGBP5-ROP5 were confirmed by Pull-down-WB. 2c: we observed a greater amount of pro-IL1β in human cells infected with RHΔROP18 than RH. Conclusions: ROP39-ROP5 and hGBP5-ROP5 interactions were confirmed by two different techniques. We model that ROP5 interacts with human GBP5 and this interaction could alter the activation of the NLRP3-inflamosome in human PBMCs in a ROP18-dependent manner.